Review of Research Evaluation, Volumes 13(3), 14(1), and 14(2) - Chris L. S. Coryn (The Evaluation Center at Western Michigan University, 2006)
Research Evaluation is a peer-reviewed interdisciplinary journal about the "methods, experiences and lessons for ex-ante and ex-post evaluation of single proposals through performances" (Research Evaluation, 2005). Given the considerable interest in evaluating research, as demonstrated by the 21 sessions sponsored by the American Evaluation Association (AEA) Research, Technology, and Development Evaluation Topical Interest Group (TIG) at the recent 2005 American Evaluation Association/ Canadian Evaluation Society jointly-sponsored conference, the journal certainly deserves coverage in the pages of JMDE. This review covers the three most recent issues of Research Evaluation (Volume 13(3), 2004; Volume 14(1), 2005; and Volume 14(2), 2005).